2000
DOI: 10.1074/jbc.275.15.11451
|View full text |Cite
|
Sign up to set email alerts
|

β(1,2)-Xylose and α(1,3)-Fucose Residues Have a Strong Contribution in IgE Binding to Plant Glycoallergens

Abstract: Primary structures of the N-glycans of two major pollen allergens (Lol p 11 and Ole e 1) and a major peanut allergen (Ara h 1) were determined. Ole e 1 and Ara h 1 carried high mannose and complex N-glycans, whereas Lol p 11 carried only the complex. The complex structures all had a ␤(1,2)-xylose linked to the core mannose. Substitution of the proximal N-acetylglucosamine with an ␣(1,3)-fucose was observed on Lol p 11 and a minor fraction of Ole e 1 but not on Ara h 1. To elucidate the structural basis for IgE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
249
0
3

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 366 publications
(256 citation statements)
references
References 65 publications
4
249
0
3
Order By: Relevance
“…Earlier reports showed that xylose is not always bound equally well by specific antibodies (31), and one study suggested that presence of ␣1,3-mannose on M3X(F) structures might interfere sterically with binding (20). In our study, three-dimensional-glycan modeling provided a first correlative and plausible explanation for altered xylose recognition.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Earlier reports showed that xylose is not always bound equally well by specific antibodies (31), and one study suggested that presence of ␣1,3-mannose on M3X(F) structures might interfere sterically with binding (20). In our study, three-dimensional-glycan modeling provided a first correlative and plausible explanation for altered xylose recognition.…”
Section: Discussionmentioning
confidence: 61%
“…Previously, van Ree et al (20) concluded that xylose-specific IgE antibodies that bound to bromelain M2XF (MUXF) N-glycan did not recognize closely related M3XF (MMXF) structures of PHA-L or HRP because of sterical hindrance caused by the presence of ␣1,3-mannose in case of M3XF (MMXF), whereas Bencúrová et al (31) concluded that bromelain is not useful for detection of xylose-specific antibodies because of an absence of ␣1,3-mannose from M2X (MUX).…”
mentioning
confidence: 99%
“…These xylose residues are attached to a different monosaccharide (and in a different linkage position) than known glycans. Therefore, it is not known whether the xylose residues reported here have allergenic natures similar to those of the xylose residues found in other known glycans [87][88]. In addition, we also do not know how the additional methyl groups affect the protein and its immunogenic response.…”
Section: Suggested Biochemical Processes Of N-glycosylationmentioning
confidence: 84%
“…This is in line with recent literature on crossreactive carbohydrate determinants. The (α1-3)-fucosylated and (β1-2)-xylosylated N-glycans have been repeatedly reported to be immunogenic in mammals [12][13][14][15][16][17] and in fact (β1-2)-linked Xyl and (α1-3)-linked Fuc residues have been identified as the epitope structures for IgE binding [18,19] in patients allergic to tree and grass pollens. The vast potential for cross-reaction of antibodies with one or both of these carbohydrate determinants is further extended by the Table 5 Survey of N-glycans obtained from gpMuc, together with their relative amounts occurrence of the same epitope structures on glycoproteins of insects, molluscs and parasitic worms [20][21][22].…”
Section: Discussionmentioning
confidence: 99%